SCHOOL ADMINISTRATION TRANSFORMATION: IMPROVING THE PERFORMANCE OF PRINCIPALS, ADMINISTRATORS, AND SCIENCE TEACHERS WITH A MANAGEMENT INFORMATION SYSTEM (SIMA) MODEL - Nasution, Satri Dwi Kurnia; Karnati, Neti; Rugaiyah, Rugaiyah (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to develop and evaluate a digital-based archive management model for a quality assurance system in elementary schools, addressing the inefficiency of traditional archiving practices and the absence of digital archive management. The research employs a Research and Development (R&D) approach using the Successive Approximation Model (SAM) and a mixed-methods strategy. The population consists of science teachers in Bekasi Regency, with data collection conducted through pre-tests and post-tests. The SIMA application was validated by three experts, followed by small-group trials with 40 teachers and large-group trials with 750 respondents. The effectiveness of the SIMA application was tested using significance testing with a paired-sample t-test. The results reveal that (1) expert validation categorized the digital-based archive management application as "Feasible" for testing; (2) small group trials yielded "Effective" results, with minor revisions; (3) large group trials confirmed the application as "Appropriate" for broader implementation; and (4) the effectiveness test showed a significant difference in respondents' understanding of archive management between pre-test and post-test scores (p = 0.001 < 0.05), indicating the application’s impact. The Archive Management Information System (SIMA) introduces a breakthrough in digital archive management at the elementary school level, offering significant efficiency, accuracy, and user satisfaction advantages. The SIMA application modernizes administrative processes and enhances the quality assurance system in schools. This research provides a practical, scalable solution for improving archiving practices in educational institutions.